Scientific evaluation of journals in Information Science: join of Impact Factor and h index indicators - Silva, Deise Deolindo [UNESP]; Almeida, Catia Candida de [UNESP]; Cabrini Gracio, Maria Claudia [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2018)
Bibliometric indicators are a relevant subsidy to the assessment process of scientific production, especially at the meso and macro level, and to decision making in scientific policies. Among them, we highlight Impact Factor and h-index. Created for the impact assessment of scientific journals, Impact Factor is defined as the citation average reached by a scientific journal in a given period. The h-index considers in its formulation aspects related to the scientific impact (citation) and productivity (number of articles produced) of a researcher. Given the contemporary importance of these indicators, this research aims to propose a evaluate procedure to scientific journals that combines Impact Factor and h-index, in order to contribute to the discussion of the need for a multidimensional evaluation in the assessment processes. The values of Impact Factor and h-index of the 168 scientific periodicals from Information Science field that are indexed in the Scopus database for years 2012, 2013, 2014 were retrieved. Among the results, it was observed that, although there is a tendency of similar positioning regarding these indicators, for a significant portion of journals the trends are discordant. It is concluded that the combined use of Impact Factor and h-index contributes to a more precise evaluation of scientific journals.
Keywords: Impact Factor; h-index; Bibliometric indicators; Journals in Information Science; Scientific evaluation